MAMPUKAH REWARD DAN PUNISHMNET MEMPENGARUHI KINERJA SUMBER DAYA INSANI PADA LEMBAGA KEUANGAN MIKRO SYARIAH (LKMS) - Septina Fitriyani; Nuri Herachwati; Moh. Safik (LP2M IAI Miftahul Ulum Pamekasan, 2022)
This study aims to answer the question about Is There an Effect of Reward on the Performance of BMT Al-Iktisab Kebun Baru East Java Employees, Is There an Effect of Punishment on the Performance of BMT Al-Iktisab Kebun Baru East Java Employees, Is There a Simultaneous Effect of Reward and Punishment on the performance of BMT employees Al-Iktisab New East Java Gardens. The research method used is quantitative research method and the type of research is correlational, with the research object namely, BMT Al-Iktisab Kebun Baru East Java. ‎Data collection techniques used Questionnaire and Observation. The research results show that there is a significant effect of reward on the performance of BMT Al-Iktisab Kebun Baru East Java employees, this can be seen from the coefficient value of the reward variable which has a significant value of 0.000 ≤ 0.05, the value of th 3.306 > tt 1.671. The influence of the punishment variable on the performance of BMT Al-Iktisab Kebun Baru East Java employees, can be seen from the coefficient value of the punishment variable which is 0.149. There is an effect of reward and punishment simultaneously or jointly on the performance variables of BMT Al-Iktisab Kebun Baru East Java employees, this can be seen from the significant value of 0.000 which is smaller than 0.05. Keywords: Reward, Punishment, Employee Performance